Pengaruh Model Pembelajaran Auditory, Intellectually, Repetition (AIR) Berbasis Video Pembelajaran Terhadap Hasil Belajar IPAS Siswa Kelas IV - Risma Erawati Purba; Dyan Wulan Sari HS; Antonius Remigius Abi; Regina Sipayung; Patri Janson Silaban (Departement of Mathematics Education, 2024)
This research aims to determine the effect of the video-based Auditory, Intellectually, Repetition (AIR) learning models on class IV students science learning outcomes UPTD SDN 122358 Siantar Martoba 2023/2024. The research method used is an experimental method with a quantitative research type. To obtain the data required a test instrument of 25 questions. The total research sample was 30 students based on purposive sampling technique. To determine students' initial abilities, the research conducted a Pre Test with an average score of 50.13 which was included in the poor category. The results of the Post Test have improved from the Pre Test results given previously with the students' average score reaching 79.47 in the good category. It can be said that the level of success in student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation, the results obtained were r_count ≥ r_tabel with results of 0.819 ≥ 0.361. Next, hypothesis testing compares the t_count ≥ t_table value. The obtained value of t_count = 7.552 while t_table = 2.048. Because t_count ≥ t_table (7.552 ≥ 2.048) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Auditory, Intellectually, Repetition (AIR) learning model (X) on student learning outcomes (Y